Pengaruh Pembelajaran Kontekstual Terhadap Kompetensi Literasi Lingkungan Mahasiswa Universitas Halim Sanusi Bandung pada Mata Kuliah Media Pembelajaran - Muhamad Ramdan Gumilar (LP2M UIN Ambon, 2026)
Contextual learning has strategic relevance for strengthening environmental literacy among pre-service primary teacher students, yet its integration in learning media courses remains predominantly technical and less contextual. This study aims to analyze the effect of Contextual Teaching and Learning (CTL) on environmental literacy competence at Universitas Halim Sanusi Bandung. The study applied a quantitative approach with a quasi-experimental nonequivalent control group design. The research population consisted of students enrolled in the Learning Media course, with a total sample of 98 students divided into experimental (n = 49) and control (n = 49) groups. The sam-ple selection procedure employed purposive sampling based on class availability and equal group size considerations. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the Wilcoxon Signed Ranks Test, and Pearson correlation. The findings indicated a signifi-cant improvement in environmental literacy in the experimental group (Sig. 0.012 ¡ 0.05) and a strong positive correlation between pro-environmental attitudes and environmental literacy scores (r = 0.684; p = 0.000). The discussion confirms CTL as an effective learning ecosystem to support both cognitive ecological understanding and affective environmental reinforcement through authentic contextual experiences. The study concludes that CTL is more effective in improving environmental literacy competence than learning without contextual intervention. It is recommended that lectur-ers adopt CTL based on local environmental issues, while institutions provide systematic support through innovative, sustainability-oriented pedagogical training.